2007
DOI: 10.1111/j.1095-8649.2007.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic variation and biogeography of catostomid fishes based on mitochondrial and nucleic DNA sequences

Abstract: The genetic variation, phylogeny and biogeography of catostomid fishes were investigated based on mitochondrial cytochrome b and nuclear 18S-ITS1-5.8S DNA sequences. The pair-wise genetic distance of cytochrome b for 17 catostomids varied considerably, from 1Á00% (Chasmistes brevirostris and Deltistes luxatus) to 23Á3% (Cycleptus elongatus and Moxostoma anisurum). The size of the 18S-ITS1-5.8S sequence ranged from 315 bp (Moxostoma robustum) to 575 bp (Ictiobus cyprinellus). The 18S-5.8S region was conservativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 35 publications
6
20
2
Order By: Relevance
“…Recent works on molecular systematics of the Catostomidae [28,29] are, on the whole, consistent with that of Smith [1] , showing differences mainly in the composition and position of the Cycleptinae. In Harris and Mayden's [28] analysis based on the mitochondrial rDNA sequences, the Cycleptinae (sensu Smith [1] ) resulted not as a monophyletic group, with Myxocyprinus as the basal-most taxon of the Catostomidae, and Cycleptus as sister to the Catostominae.…”
Section: Early Divergence Of Catostomidsmentioning
confidence: 53%
See 3 more Smart Citations
“…Recent works on molecular systematics of the Catostomidae [28,29] are, on the whole, consistent with that of Smith [1] , showing differences mainly in the composition and position of the Cycleptinae. In Harris and Mayden's [28] analysis based on the mitochondrial rDNA sequences, the Cycleptinae (sensu Smith [1] ) resulted not as a monophyletic group, with Myxocyprinus as the basal-most taxon of the Catostomidae, and Cycleptus as sister to the Catostominae.…”
Section: Early Divergence Of Catostomidsmentioning
confidence: 53%
“…They suggested setting up a new subfamily Myxocyprininae to include only Myxocyprinus asiaticus from China and confine the Cyclepitinae to the two species of Cycleptus from North America. Sun et al [29] , based on the analysis of mitochondrial cytochrome b and nuclear 18S-ITS1-5.8S DNA sequences, suggested that catostomids began to diverge in the early or mid-Miocene, which agrees with the fossil evidence known from North America. With the discovery of †Plesiomyxocyprinus arratiae the divergence time of the Catostomidae goes further back, at least, to the middle of the Eocene or even earlier.…”
Section: Early Divergence Of Catostomidsmentioning
confidence: 54%
See 2 more Smart Citations
“…According to recent phylogenetic analyses (Sun et al 2007, Doosey et al 2010, Chen and Mayden 2012, Ictiobus Rafinesque and Carpiodes Rafinesque, which belong to the monophyletic subfamily Ictiobinae, represent two of the oldest lineages of suckers. Within the most derived subfamily Catostominae, phylogenetic position of M. melanops is not well resolved (Doosey et al 2010, Chen andMayden 2012).…”
Section: Discussionmentioning
confidence: 99%